Perceptions of climatic variability among millet farmers: insights from tribal communities in the Kolli Hills, Tamil Nadu, South India - Chapke, Rajendra R.; Satyavathi, C. Tara; Israel Oliver King, E. D.; Laxmiprasanna, Peddiveeti; Priyanka, Vavilala (Frontiers in Climate, 2025)
Climate change has a diversified impact on the accessibility to resources and maintaining food security for the growing population. In this era, climate-resilient crops such as millet have greater importance and impact on the food security of the nation. Millet cultivation in tribal areas of India presents a unique example of resilience in response to climatic variability. The research was conducted in the Kolli Hills of the Namakkal district in the state of Tamil Nadu to study the tribal farmers’ perception of climate change. Data were collected from 125 tribal farmers from five villages using a multistage random sampling method and a verified semi-structured interview schedule. Both qualitative and quantitative data were collected for analysis with different statistical tools. The majority of tribal farmers were found to be in the young age, with a high level of illiteracy and had less than 1.5 hectares of land with low mass media utility and limited decision-making ability. It was revealed that in recent years occurrences of drought, untimely rains, temperature fluctuations, and irregular weather conditions have increased. Most of the tribal farmers perceived that climate change substantially impacts low-resourced farmers’ ability to secure their livelihoods. Social participation and mass media utilization were positively correlated with tribal farmers’ perception of climatic variability. Scientific institutional knowledge and local community knowledge must be integrated with the farmers’ experiences of climate change to enable them to minimize the effect of climate change on millet production and develop a strategy that improve production under future climate scenarios. The study recommends the integration of traditional millet farming practices with modern agricultural techniques as well as the need for targeted policies that strengthen institutional support, market access, and capacity-building initiatives for tribal farmers.